Zooarchaeology in Lithuania - Piličiauskienė, Giedrė; Micelicaitė, Viktorija (Archaeologia Lituana, 2020)
In recent years Lithuanian archaeologists have become greatly more aware of and interested in the information provided by faunal remains. Its potential has begun to draw the attention of researchers from nature sciences, while the archaeologists working in the field collect faunal remains uncovered during excavations and hand them over for storage increasingly more often. These faunal remains continue to be stored in the repository at Vilnius University. The project carried out in 2018–2020 with the funds provided by the Research Council of Lithuania gave an opportunity to record and make public the information about the zooarchaeological finds stored in the repository of Vilnius University, which are accessible for researchers and students from various scientific fields. The aims of this article are to present the Lithuanian collection of faunal remains kept at Vilnius University, to review the history of zooarchaeological research as well as the studies carried out in the last few years and to discuss the associated problems that continue to emerge.